Electronic and Optical Properties of ZnAl2Se4 and Its Use in Solar Cell. Issue 1 (18th December 2017) - Sahariya, Jagrati; Kumar, Pancham; Soni, Amit; Bhamu, K. C.
Abstract : The present paper deals with the electronic and optical properties of ZnAl2 Se4 chalcopyrite compound via full potential linearized augmented plane wave method as embodied in Wien2k code of Vienna group. All the calculations are done using the most accurate modified Becke and Johnson (mBJ) potential. We report energy bands, total and partial density of states, absorption spectra, real and imaginary components of dielectric function, reflectivity and refractivity spectra of ZnAl2 Se4 compound. Energy gap of ZnAl2 Se4 is found to be 3.30 eV which is in accordance with the reported experimental data. High intensity of absorption spectra in visible range (3–5 eV) for ZnAl2 Se4 shows its utility for optoelectronic applications such as solar cell.